Weak Solutions of a Stochastic Model for Two-Dimensional Second Grade Fluids. (9th March 2010) - Razafimandimby Razafimandimby, P. A. P. A.; Sango Sango, M. M.
Abstract : We initiate the investigation of a stochastic system of evolution partial differential equations modelling the turbulent flows of a second grade fluid filling a bounded domain of ℝ 2 . We establish the global existence of a probabilistic weak solution.